Application of the Proportionality Principle in Consumer Dispute Resolution through the Consumer Dispute Settlement Body (BPSK) - Lina Maulidiana; Rendy Renaldy; Salsabila Mareta Rizal (Dinasti Research, 2024)
The Principle of Proportionality in Consumer Dispute Resolution through the Consumer Dispute Settlement Body (BPSK) must be considered to ensure that neither party is disadvantaged. Based on problem identification, the purpose of this research is to analyze the application of the proportionality principle in resolving consumer disputes by BPSK through a conflict resolution model that is fair, honest, and capable. The research method used is applied research, a type of research whose results can be directly applied to solve the current problem, using a normative applied approach. The data used consists of secondary data collected through literature study techniques and analyzed qualitatively. The research results show that the application of the principle of proportionality implies the existence of balance and refers to the exchange of rights and obligations in all legal relationships, which does not always achieve the same mathematical balance. Therefore, differences in outcomes are considered fair and acceptable if the exchange of rights and obligations is proportional. The suggestion in this study is the need for specific regulations regarding consumer dispute resolution through the Consumer Dispute Settlement Body (BPSK) via a one-stop service.